INTEGRATED PLANT nUTRIENT management - Singh, Ranbir; Kumar, Ashok; Shivakumar, B G (Indian Farming, 2015)
The basic concept underlying IPNM is the maintenance oradjustment of soil fertility and of plant nutrient supply to an optimum level for sustaining the desired crop productivity through optimization of the benefits from all possible sources of plant nutrients such as chemical fertilizer, organic manures, biofertilizersetc in an integrated manner.